Development of E-Modules in Increasing Digital Literacy in Islamic Religious Education Subjects: An Effort to Support the Implementation of the Kurikulum Merdeka - Hamdi; Jumrodah (Jurnal Pendidikan Agama Islam Al-Thariqah, 2023)
This study aims to describe the development of e-modules in improving digital literacy in Islamic religious education subjects, as an effort to support the implementation of an independent curriculum. This study uses field research that uses qualitative methods with a phenomenological approach, the research informant consists of key informants are Islamic class IV religious education teachers while additional informants are school principals, curriculum wakame, and grade IV students. Data collection techniques using interview research instruments, while data analysis techniques using Miles and Huberman include: reviewing and digging data to obtain saturated data and collecting data, reducing data, presenting data, and making conclusions. The results obtained in this study are the development of e-modules is very appropriate as an effort to support the implementation of an independent curriculum and as a strengthening of digital literacy in improving the intelligence of students through the cultivation of religious character and discipline in carrying out dhuha prayers in Islamic Religious Education subjects. It is hoped that in the future teachers can be more creative in designing e-modules so that students will more easily understand and provide a fun learning experience